Hubungan Pengetahuan Dan Sikap Calon Pengantin Wanita Terhadap Pemberian Imunisasi Tetanus Toksoid (TT) Di Wilayah Kerja UPT Puskesmas Moro Kecamatan Moro - Nurrizam Nurrizam; Rachmawaty M. Noer; Mira Agusthia (Lembaga Pengembangan Kinerja Dosen, 2024)
Tetanus Toxoid (TT) immunization is the provision of tetanus immunization to women of childbearing age (WUS) or who are pregnant. This action is the easiest and most effective preventative measure against neonatal tetanus. Objective: This study aims to determine the relationship between knowledge and attitudes of prospective brides and grooms regarding the provision of tetanus toxoid (TT) immunization in the Moro Community Health Center UPT Working Area, Moro District. Method: Quantitative research type with a cross sectional approach, total population is 54 populations with total sampling. The questionnaire research instrument and Univariate and Bivariate data analysis used Chi-Square. Results: Characteristics based on age of the 54 prospective bride and groom respondents aged (20-35 years) were 52 (96.3%), 28 (51.9%) had a high school education, 34 (63.0%) did not work. Results: Chi-square analysis shows a p-value of 0.000 (p<0.05) so there is a relationship between the prospective bride's knowledge and tetanus toxoid (TT) immunization and the results of the Chi-square analysis show a p-value of 0.020 (p<0.05 ) so that there is a relationship between the attitude of the prospective bride and the tetanus toxoid (TT) immunization. Conclusion: The bride and groom's knowledge about TT immunization was mostly less than 36 (66.7%) and the bride and groom's attitude about TT immunization was the most negative attitude, 31 (57.4%).